The Contribution of COL4A5 Splicing Variants to the Pathogenesis of X-Linked Alport Syndrome - Yamamura, Tomohiko; Horinouchi, Tomoko; Aoto, Yuya; Lennon, Rachel; Nozu, Kandai (Frontiers in Medicine, 2022)
X-linked Alport syndrome (XLAS) is caused by pathogenic variants in COL4A5 and is characterized by progressive kidney disease, hearing loss and ocular abnormalities. Recent advances in genetic analysis and further understanding of genotype-phenotype correlations in affected male patients raises the importance of detecting splicing variants in COL4A5. Aberrant splicing of COL4A5 is caused not only by canonical splice site variants but also non-canonical splice site variants such as deep intronic changes or even substitutions in exons. Patients with splicing variants account for approximately 15% of all cases in XLAS. In addition, it has been shown that there is a significant difference in kidney survival depending on the aberrant splicing patterns of transcripts- in particular in-frame or out-of-frame nucleotide changes in transcripts. Therefore, cDNA analysis of patient mRNA is necessary to determine the impact of splice site variants and to confirm a diagnosis of XLAS and to predict the kidney prognosis. However, it is usually difficult to amplify COL4A5 transcripts extracted from peripheral blood leukocytes. For these cases, in vitro minigene assays or RNA sequence extracted from urine derived cells can confirm aberrant splicing patterns. Moreover, controlling aberrant splicing by nucleic acids or small molecular compounds in genetic diseases are attracting attention as a potential therapeutic strategy. Here, we review the frequency of splicing variants in COL4A5, the latest diagnostic strategies, and the prospects for new therapeutic approaches.